Impact of road provision a case in Mindanao's agriculture sector - Sarip, Normala Junnah Laluna (UP Mindanao, 2007)
This study was conducted to analyze the impact of road provision to agricultural income in selected regions of Mindanao. In particular, this study focuses on the impact of road provision to Gross Value Added in Agriculture (GVAA) with further analysis in different classifications (e.i. national and local) as well as in different types of roads (e.i.) paved and unpaved). Analysis on roads is segregated into two groups that are national versus local, and paved versus unpaved in order to establish comparison between the significance of each group. The study spans for 20 years that is from 1983 to 2002 and covers only four regions namely: Region 9 (Western Mindanao), Region 10 (Northern Mindanao), Region 11 (Southern Mindanao), and Region 12 (Central Mindanao). The two regions, Autonomous Region in Muslim Mindanao (ARMM) and CARAGA, were not included in this study since they are recently, established and no sufficient data on these regions are available. The study found out that local roads had larger impact than national roads while unpaved roads provide larger benefits than paved roads. As a whole, lag GVAA had significant impact to agricultural income in Mindanao. And there were also signs of time lags between the construction and impact of roads since roads of the prior year (for local, paved, unpaved and total road network) were also significant.